An iterative method for the inverse kinematics of lower-mobility parallel mechanism with three RS or SR chains based on kinematically equivalent mechanism. (November 2019) - Liang, Xinghai; Takeda, Yukio
Highlights: An iterative method for the inverse kinematics of lower-mobility parallel mechanism. The method is based on the 6-DOF kinematically equivalent mechanism. It solves the inverse kinematics without formulating tedious constraint equations. It includes various structural parameters in a unified model. Abstract: This paper presents an iterative method for solving the inverse kinematics (IK) of lower-mobility parallel mechanisms (LMPMs) with three RS or SR chains based on the kinematically equivalent mechanism (KEM). KEM is a virtual parallel mechanism with 6 DOF having the same motion as the original LMPM under the actuated joint motion constraints. The method enables us to solve the IK of such parallel mechanisms considering various structural parameters and different sets of output degrees of freedom (DOF) in a unified way, yet without formulating conventional constraint equations. As a demonstration, an iterative procedure for solving the IK of a 3-P RS parallel mechanism based on its KEMs is presented. Numerical examples show the process in solving the IK of the LMPMs considering different sets of output DOFs and various structural parameters using the proposed method.